Adaptive low-power CMOS LNA in internet of things based wireless sensor networks - Helali, Abdelhamid; Ouni, Feten; Nasri, Mohsen; Maaref, Hassen (International Journal of Engineering and Technology, 2020)
With the increasing need for the Internet of things (IoT), wireless communication has become a popular technology for the network. This explosion of IoT wireless applications makes the power consumption a key metric in the design of wireless sensor nodes. The major constraint of the wireless sensors nodes is battery energy, which is the mainly challenging problem in designing IoT network. these constraints have imposed new yet stringent specs to the design of RF front-ends. The design of adaptive radio-frequency circuits, in order to reduce power consumption, is of interest. In a RF receiver chain, the Low Noise Amplifier (LNA) stand as critical elements on the power consumption.To address this purpose, this paper proposes a design strategy for an adaptive Low Noise Amplifier as the first element of the receiver chain. Hence the proposed LNA achieves the correct QoS for various scenario of communications. Using the proposed LNA, a significant trade-off between a conversion gain, noise figure and energy consumption is presented.Â Â